1990
DOI: 10.1016/0014-5793(90)81238-j
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the RNase H domain of HIV‐1 reverse transcriptase expressed in recombinant Escherichia coli

Abstract: The ribonuclease H (RNase H) domain of human immuno-deficiency virus (HIV-l) reverse transcriptase has been produced with the aim of providing sufficient amounts of protein for biophysical studies. A plasmid vector is described which directs high level expression of the RNase H domain under the control of the I PL promoter. The domain corresponds to residues 427-560 of the 66 kDa reverse transcriptase. The protein was expressed in Escherichia cob' and was purified using ion-exchange and size exclusion chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…The p15 RNase H domain of HIV-1 exhibits structural similarity to Escherichia coli RNase H (36). But unlike the E. coli RNase H, which cleaves the RNA component of RNA/DNA duplexes randomly, the isolated p15 of RT has been shown to be devoid of RNase H function (36,37). In combination with the data available in the literature (18, 20, 21, 36 -42), our results strongly support the notion that in the absence of structural elements responsible for RT positioning on the polynucleotide substrate, the RNase H active site is rendered inactive.…”
Section: Discussionsupporting
confidence: 84%
“…The p15 RNase H domain of HIV-1 exhibits structural similarity to Escherichia coli RNase H (36). But unlike the E. coli RNase H, which cleaves the RNA component of RNA/DNA duplexes randomly, the isolated p15 of RT has been shown to be devoid of RNase H function (36,37). In combination with the data available in the literature (18, 20, 21, 36 -42), our results strongly support the notion that in the absence of structural elements responsible for RT positioning on the polynucleotide substrate, the RNase H active site is rendered inactive.…”
Section: Discussionsupporting
confidence: 84%
“…3A). RNH102 was inactive under these conditions, and as has been observed by others (10,(37)(38)(39), the wild-type HIV-1 domain was also inactive. Very different results were obtained when Mn2+ was substituted for Mg2+ as the divalent cation (Fig.…”
supporting
confidence: 50%
“…The importance of this region for substrate binding has been demonstrated in several studies. The RNase HI domain isolated from HIV-1 reverse transcriptase is enzymatically inactive (13,14), whereas that from murine leukemia virus reverse transcriptase, which has a part of this region, is active (15,16). Site-directed mutagenesis indicated that the positively charged residues in this region are important for substrate binding (17).…”
mentioning
confidence: 99%